Unusual 9,19 : 24,32-Dicyclotetracyclic Triterpenoids from Lygodium japonicum - Han, Qing-hua; Liu, Xin; Yao, Wen-qing; Cheng, Zhong-bin; Lin, Ting-ting; Song, Ching; Yin, Sheng (Planta Medica, 2012)
Lygodipenoids A (1) and B (2), two novel C33 tetracyclic triterpenoids with a new 9,19 : 24,32-dicyclopropane skeleton, were isolated from the whole grass of Lygodium japonicum. Their structures were elucidated by spectroscopic and chemical means. Compounds 1 and 2 were tested in transfected cultured human embryonic kidney 293 HEK293 cells for an agonist assay, and compound 1 was identified as a partial agonist for liver X receptor α.
Keywords: >Lygodium japonicum (Thunb.) Sw.; Lygodiaceae; 9,19 : 24,32-dicyclotetracyclic triterpenoid; liver X receptor α